Copper Does Not Induce Tenogenic Differentiation but Promotes Migration and Increases Lysyl Oxidase Activity in Adipose-Derived Mesenchymal Stromal Cells. (20th February 2020) - Milewska, Marta; Burdzińska, Anna; Zielniok, Katarzyna; Siennicka, Katarzyna; Struzik, Sławomir; Zielenkiewicz, Piotr; Pączek, Leszek
Abstract : Background . Copper belongs to the essential trace metals that play a key role in the course of cellular processes maintaining the whole body's homeostasis. As there is a growing interest in transplanting mesenchymal stromal cells (MSCs) into the site of injury to improve the regeneration of damaged tendons, the purpose of the study was to verify whether copper supplementation may have a positive effect on the properties of human adipose tissue-derived MSCs (hASCs) which potentially can contribute to improvement of tendon healing. Results . Cellular respiration of hASCs decreased with increasing cupric sulfate concentrations after 5 days of incubation. The treatment with CuSO4 did not positively affect the expression of genes associated with tenogenesis ( COL1α1, COL3α1, MKX, and SCX ). However, the level of COL1 α 1 protein, whose transcript was decreased in comparison to a control, was elevated after a 5-day exposition to 25 μ M CuSO4 . The content of the MKX and SCX protein in hASCs exposed to cupric sulfate was reduced compared to that of untreated control cells, and the level of the COL3 α 1 protein remained unchanged. The addition of cupric sulfate to hASCs' medium increased the activity of lysyl oxidase which was positively correlated with concentration of CuSO4 . Moreover, a high level of CuSO4 stimulated the action of intracellular superoxide dysmutase. The hASC secretion profile after a 5-day exposure to 50 μ M cupric sulfate differed from that of untreated cells and was similar to the secretion profile of human tenocytes. Additionally, cupric sulfate increased secretion of CXCL12 in hASCs. Furthermore, the exposition to the CuSO4 significantly increased directed migration of human ASCs in a dose-dependent manner. Conclusion . Copper sulfate supplementation can have a beneficial effect on tendon regeneration not by inducing tenogenic differentiation, but by improving the recruitment of MSCs to the site of injury, where they can secrete growth factors, cytokines and chemokines, and prevent the effects of oxidative stress at the site of inflammation, as well as improve the stabilization of collagen fibers, thereby accelerating the process of tendon healing.